Training day [videorecording (DVD)] - Fuqua, Antoine; Washington, Denzel, 1954-; Hawke, Ethan, 1970-; Glenn, Scott, 1942-; Berenger, Tom, 1949- (Warner Home Video, 2002)
Jake Hoyt, a fresh-faced rookie in the Los Angeles Police Department, gets a chance to join the elite narcotics squad headed up by 13-year veteran Detective Sergeant Alonzo Harris. Jake is to prove himself during a one-day ride-along. As the day wears on, it becomes increasingly clear that Detective Harris has blurred the line between right and wrong to an alarming degree, enforcing his own code of ethics and street justice. Eventually, Hoyt begins to suspect that he is, rather than having the opportunity to join the squad, being set up to take the fall.